PENGARUH MARKETING MIX 4P (PRODUCT, PRICE, PLACE, PROMOTION) JNE TERHADAP LOYALITAS PELANGGAN JNE MELALUI VARIABEL INTERVENING KEPUASAN PELANGGAN JNE - Isfansyah, Haikal Ayasya; Widodo, Arry (FEB Universitas Sam Ratulangi Manado, 2024)
The development of the internet and the increasing volume of e-commerce shopping in Indonesia has had a major impact on business, especially shipping/logistics services such as JNE. In 2020, JNE has the highest sales after J&T, this encourages the company to create satisfaction and loyalty for customers through implementing the 4P Marketing Mix. This research aims to analyze the influence of JNE's 4P Marketing Mix on Customer Loyalty with Customer Satisfaction as an intervening variable. The research used a quantitative approach and descriptive analysis, with a non-probability sampling technique on 404 respondents using a Likert scale. Data was analyzed using the Partial Least Square method with SmartPLS. The research results show that Marketing Mix 4P has a positive and significant effect on Customer Satisfaction. Customer Satisfaction also has a positive and significant effect on Customer Loyalty. Apart from that, Marketing Mix 4P has a positive and significant effect on Customer Loyalty, both directly and through Customer Satisfaction as an intervening variable. This research confirms the importance of the 4P Marketing Mix strategy in increasing JNE customer satisfaction and loyalty. Keywords: Marketing Mix 4P, Customer Satisfaction, Customer Loyalty